Development of Learning Design Module on P5 Learning: Improve HOTS of Vocational Students - Nurfaizana, Della Rulita; Churiyah, Madziatul; Basuki, Andi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The implementation of Merdeka Curriculum in all educational units in Indonesia has a significant impact on the learning elements in it, including the impact on Vocacional School, which is a school with high demands for learning independence. This research aims to produce a learning design module product on P5 learning, especially the theme of work. Learning design module on P5 learning especially the theme of work has been developed through 3 steps: 1) Preliminary study, 2) Product development, 3) Product testing. The module was developed with the following elements: 1) Module profile and module objectives, 2) Subtheme 1 (self-recognition), 3) Assessment Rubric for Subtheme 1, 4) Reflection Sheet Subtheme 1, 5) LKPD Sub-theme 1, 6) Sub-theme 2 (equip yourself), 7) Subtheme 2 Assessment Rubric, 8) Reflection Sheet Sub Theme 2, 9) LKPD Sub Theme 2, 10) Subtheme 3 (Ability to Communicate Effectively), 11) Subtheme 3 Assessment Rubric, 12) Reflection Sheet for Sub Theme 3, 13) LKPD for Sub Theme 3, 14) Subtheme 4 (Exploration of Local Potential), 15) Rubric for Assessment of Subtheme 4, 16) Reflection Sheet for Sub- theme 4, 17) LKPD Sub Theme 4. Based on the results of product testing by media experts, material experts, and practitioners, it was found that more than 97% of the substance in the module was suitable for use and in accordance with the needs of learners.